Steps in a long journey : community projects and sustainable development in west Kwaio and central Kwara'ae, Malaita, Solomon Islands : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Roura, Ricardo (Massey University, 2001)
This study attempts to evaluate whether development projects could be means to the end of sustainable development in the Solomon Islands context of a subsistence economy in transition to a cash economy. Literature on development often emphasizes theory over practice, global over local, project design and implementation over project evaluation, and failures over successes. This research intends to reverse these tendencies and determine, in the evaluation of highly participatory, highly local, small-scale community projects, whether development projects could be means to the end of sustainable development. The evaluation is based on the assumption that community projects can only be truly successful if they contribute to maintain and/or improve the condition of both people and the ecosystem. It is proposed here that sustainable development may be realized through the cumulative effect of development activities that may be individually minor—at a local or a higher level—but collectively significant. What is inherently difficult is how the collective result of many disparate local development initiatives in the present may result in a desired state of affairs in the future—not just locally, but at a national or regional level. It is concluded here that community projects may contribute to progress towards sustainable development but are not a sufficient means to this end. Projects may have a tactical role in development, but should be integrated to an overall strategy for sustainable development. Ultimately these needs may lead to a new development practice paradigm that replaces the project. A new paradigm should be inclusive of emerging initiatives at the grassroots level, but also fit in a broader strategy for sustainable development. The search for a long term development strategy, however, should not impede local action to address more immediate needs. On line with research by others in this issue, it argued here that in the Solomon Islands the notion of community is interwoven with the land through present use and history in the notion of fanua kem, "our place". The notion of fanua could provide a cultural foundation to the notion of sustainable development. It is suggested that the value of fanua results not so much a matter of awareness of superior goals but rather, it is in the quotidian quality and ubiquitous use in Solomon Islands villages that the notion of "our place" does provide a sense of identity and belonging to a place, a community, a common past, and a common future.
Keywords: Malaita, Solomon Islands; Community development; Rural development; Sustainable development